Demography and morphometry of an important mesopredator (black-backed jackal - Canis mesomelas) in southern Africa - de Waal, HO, author; Combrinck, Wliie, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Predation losses on livestock and wildlife ranches are more than ZAR 2 thousand million per year. The black-backed jackal Canis mesomelas is an important mesopredator in South Africa and Namibia and implicated for much of these losses. Despite control over decades, little is known about their demography and morphometry. Information was collected by farmers and specialist predator hunters during a period of 21 months. Time of year hunted (age relative to whelping), eruption of the permanent teeth and the wear of incisors were used to categorise 4 age groups: <0.5 years (pups), 0.5–1 years (juveniles), between 1–2 years (yearlings), and ≥2 years (adults). The 455 males and 411 females did not support the assumption that hunted (stressed) populations respond by producing more females to increase reproductive fitness of the species. Except for significantly more females in the age group 1-2 years (yearlings), their sex ratio was not skewed. Sexual dimorphism was evident with males weighing consistently more than same age females; the heaviest adult male and female weighed 12.5 kg and 11.5 kg, respectively. Growth and development of black-backed jackals occurred mostly in the first 6months of their lives, thereafter decreasing gradually. Sexual dimorphism was also displayed by morphometry and total body length, body length and tail length of males were consistently more than for females. Predation management of black-backed jackals must be informed by good knowledge of the interface between its biology and management; this information is now used to develop meaningful coordinated predation management strategies.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.